Students’ perception and effectiveness of learning human structure and functions II (AHS 1023) through problem-based learning (PBL): a preliminary study - Mohd Amin, Nor Munirah; Yusof, Nurul Asyiqin; Zamli, Zaitunnatakhin (Universiti Kebangsaan Malaysia ( UKM ), 2019)
Introduction: Anatomy is a prerequisite course for other courses in the health based programmes. Realizing that basic understanding of anatomy is vital to understand clinical subjects in the later semesters, problem-based learning (PBL) is implemented to supplement the lecture sessions. However, previous studies have showed inconsistent findings on the effectiveness of PBL in teaching and learning anatomy. Thus, the present study aimed to evaluate students’ perception and effectiveness of learning the Human Structure and Functions II (AHS 1023) through the PBL.